INVESTIGATING THE OPTICAL LOSSES OF A SECOND REFLECTOR IN A BEAM DOWN POWER TOWER - Shiun, Onn Wei (IRC, 2016)
Concentrated Solar Energy (CSP) is the new technology today to concentrating large area of sunlight to a spot on the solar receiver. High concentration of light will elevate the temperature to a higher degree and thus heat up the heat transfer fluid(HTF). The heat transfer fluid will later heat up the water to generate steam to steam turbine to generate power. The solar site in Universiti Teknologi Petronas (UTP) is now using power tower concept which is to reflect all the light from the heliostats to the solar receiver on the top of the tower. However, this design contains a few disadvantages such as difficult to maintain, low sustainability in windy condition due to heavy installment on top of the tower, required extra pumping power and high thermal lost while transferring HTF.